FUNCTIONAL STATE OF THE LIVER RATS UNDER CONDITIONS OF STREPTOZOTOCIN-INDUCED DIABETES - Боднарчук, Ю.В.; Жураківська, О.Я.; Перцович, В.М.; Pertsovych, V.M.; Жураківський, В.М.; Кочерга, З.Р. (World of Medicine and Biology, 2016)
The experiment studied the functional changes in the liver of mature rats at different stages of development and course of streptozotocin-induced diabetes. The study was conducted on 12-month-old rats Wistar. Diabetes modeled by single intraperitoneal streptozotocin administration at a dose of 6 mg for 100 g body weight diluted in 0.1M citrate buffer (pH 4.5). It was established that in streptozotocin-induced diabetes, against hyperglycemia and elevated levels of glycosylated hemoglobin, an increase in liver enzymes in serum and liver homogenates from alaninaminotrasferazy prevalence, increasing Ritisa ratio, which indicates the violation of the functional state of the liver due to destructive changes of hepatocytes.
Keywords: liver; liver transaminases; streptozotocin-induced diabetes